Analisis Layanan Perpustakaan Desa Beran Dalam Meningkatkan Minat Literasi Warga - Kharisma Yogi Fitriana; Kharina Concetta; Iwana Abharin Izzati Azalia (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to examine the role, effectiveness, and implementation of the Beran Village Library Service in improving the reading interest and literacy of the community, as well as to identify the supporting factors, challenges, and development strategies. The study employed a descriptive qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the Beran Village Library has performed its fundamental functions and possesses considerable potential, supported by adequate facilities, an Online Public Access Catalog (OPAC), digital services, and a collection of more than 3,000 books. However, its utilization remains low due to the limited number of active members. The main challenges include the limited availability of library staff who also serve as village officials, insufficient collection updates, limited operational funding, and community concerns about the risk of damaging borrowed books. To enhance literacy, the library has implemented innovative outreach programs, such as establishing Literacy Corners at community health posts and conducting read-aloud activities tailored to community needs. The study concludes that improving village library services requires not only adequate collections and technological infrastructure but also dedicated personnel, innovative and interactive programs, and strong collaboration among the village government, library managers, and the local community.